7-HIDROKSI-6-METOKSI KUMARIN (SKOPOLETIN) DARI KULIT BATANG Chisocheton celebicus (MELIACEAE) - Katja, Dewa G.; Sonda, Andre A.; Huspa, Desi Harneti P.; Mayanti, Tri; Supratman, Unang (Jurnal Kimia (Journal of Chemistry); Vol. 9, No. 2 Juli 2015, 2015)
7-hydroxy-6-methoxy coumarin (scopoletin) has been isolated from the bark of Chisocheton celebicus (Meliacee) using several chromatographic techniques.  The chemical structure of 7-hydroxy-6-methoxy coumarin was identified on the basis of spectroscopic data including UV, IR, 1D-NMR, 2D-NMR and mass along with by comparison with those spectral data previously reported. The discovery of scopoletin from the bark C. celebicus reported for the first time in this study.
Keywords: Chisocheton celebicus, coumarin, scopoletin, Meliaceae